Downstream thoracic endovascular aortic repair following zone 2, 100-mm stent graft frozen elephant trunk implantation. (29th November 2021) - Kreibich, Maximilian; Siepe, Matthias; Berger, Tim; Kondov, Stoyan; Morlock, Julia; Pingpoh, Clarence; Beyersdorf, Friedhelm; Rylski, Bartosz; Czerny, Martin
Abstract: OBJECTIVES: The aim of this study was to analyse outcomes of downstream thoracic endovascular aortic repair (TEVAR) following the frozen elephant trunk (FET) procedure. METHODS: Sixty-six patients underwent downstream TEVAR following the FET procedure to treat thoracic aortic dissections ( n = 42, 64%), aneurysms ( n = 19, 29%) or penetrating aortic ulcers involving the aortic arch ( n = 5, 8%). Patient and outcome characteristics were analysed. RESULTS: Downstream TEVAR was performed 7 [interquartile range: 2–18] months after the FET procedure in 39 male (59%) and 27 female (41%) patients aged 68 [interquartile range: 56, 75] years, including 11 patients (17%) with a connective tissue disease. Before TEVAR, cerebrospinal fluid drainage was put in place in 61 patients (92%). Patients were treated with 1 stent graft ( n = 28, 42%), 2 stent grafts ( n = 37, 56%) or 3 stent grafts ( n = 1, 2%). The femoral artery was accessed through surgical cut-down ( n = 15, 23%) or percutaneously ( n = 49, 74%). One patient (2%) developed a temporary spinal cord injury that resolved spontaneously. No case of permanent spinal cord injury, stroke or death was observed. After 12 [interquartile range: 2–23] months, 15 patients required an additional aortic reintervention (endovascular: n = 6; surgical: n = 9). CONCLUSIONS: Downstream TEVAR following the FET procedure is associated with excellent clinical outcomes. We thus maintain that staging thoracic aortic repair—FET and secondary TEVAR—is a very successful and safe strategy. Certain patients might need a tertiary procedure to fix their entire aortic pathology; therefore, they will require long-term continuous follow-up, ideally in a dedicated aortic clinic. Abstract : The frozen elephant trunk (FET) technique has become a well-established treatment option for patients presenting all thoracic aortic pathologies including acute and chronic dissection, aortic aneurysms and even penetrating aortic ulcers involving the aortic arch and descending aorta [1–4].